“Proyecto de Inversión para la Producción y Comercialización de Aliños Artesanales en la Ciudad de Loja” - Armijos Villavicencio, Anderson Patricio (2025)
By conducting the following studies, the following paper, titled Investment Project for the Production and Marketing of Handmade seasoning in the City of Loja, fulfills the project's specific objectives: market research, technical, organizational, financial and financial evaluations. This study was conducted in a descriptive, non-experimental manner using a mixed qualitative and quantitative approach, using survey techniques and direct observation to gather information. After determining the market segment, which consisted of 62,927 families in the city of Loja, the urban population, where a total of 985,370 units of handmade seasoning were found to be unmet. A marketing plan was developed to introduce a product that is tailored to the tastes and preferences of consumers and attain a position within that market, then a technical study that determined the location of the project, which will be in the neighborhood of Zamora Huayco. The project has an installed capacity of 52,416,000 grams per year, and a used capacity of 12,480,000 grams per year of seasoning. In addition, the company will be constituted as a Rimpe entrepreneur. The initial investment will be $8,385.83 dollars, financed through Ban Ecuador with a loan of $3,700.00 dollars. Finally, the financial evaluation showed data with a positive NPV (net present value) of $23,139.08 a TIR (Internal Rate of Return) of 86%, the RBC (Benefit-Cost Ratio) of 0.18 cts., the PRC (Capital Recovery Period) of 1 year, 3 months and 4 days of life of the project, in addition to a sensitivity with an increase in costs of 0.96% and with a decrease in income of 0.96%, obtaining a feasible project.